The Role of Islamic Economics Literacy and Religiosity in Increasing Attitude and Behavior Environmental Awareness - Mustofa, Ubaedul; Widiyanto, Widiyanto; Sehabuddin, Ahmad; Aulia, T. A. P.; Pramudita, A. (Universitas Negeri Semarang, 2023)
Environmental issues have become a global issue today. Based on the Environmental Performance Index 2022, Indonesia has only been ranked 164 of the 180 countries listed. This study aims to determine whether knowledge and understanding of Islamic economic values can increase awareness of the environment. This type of research is quantitative, with the variables Islamic Economics Literacy, Religiosity, Environmental Awareness Attitude, and Environmental Awareness Behavior. This study uses a population in the Islamic economic community or Masyarakat Ekonomi Syariah (MES) of Central Java, Indonesia, with a total sample of 200 respondents. Data analysis uses the SEM-PLS technique using WarpPLS 7.0. The study results in show that Islamic economic literacy can directly or indirectly improve attitudes and behavior toward caring for the environment. The theoretical implications of the results of this research certainly further strengthen the existing concepts and theories in Islamic economics, which emphasise the importance of protecting the environment. As for the practical implications, the results of this research can be used as a basis for stakeholders to continue implementing Islamic economic education programs to solve natural environmental problems through increasing awareness of the environment.